2008
DOI: 10.3844/ajbbsp.2008.146.166
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rodent Model of Autism: Intraventricular Infusions of Propionic Acid Increase Locomotor Activity and Induce Neuroinflammation and Oxidative Stress in Discrete Regions of Adult Rat Brain

Abstract: Innate neuroinflammatory changes, increased oxidative stress and disorders of glutathione metabolism may be involved in the pathophysiology of autism spectrum disorders (ASD). Propionic acid (PPA) is a dietary and gut bacterial short chain fatty acid which can produce brain and behavioral changes reminiscent of ASD following intraventricular infusion in rats. Adult Long-Evans rats were given intraventricular infusions of either PPA (.26M, 4µl animal −1 ) or phosphate buffered saline (PBS)vehicle, twice daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 140 publications
(166 reference statements)
9
69
0
1
Order By: Relevance
“…Previous studies in rats by MacFabe et al have shown that intraventricular administration of propionate induces behaviors resembling autism (e.g., repetitive dystonic behaviors, retropulsion, seizures, and social avoidance) (12,13). We have also reported increased fecal propionate concentrations in ASD children compared with that in controls in the same fecal samples (25).…”
Section: Vol 77 2011 Lower Abundance Of a Muciniphila In Asd Childsupporting
confidence: 55%
“…Previous studies in rats by MacFabe et al have shown that intraventricular administration of propionate induces behaviors resembling autism (e.g., repetitive dystonic behaviors, retropulsion, seizures, and social avoidance) (12,13). We have also reported increased fecal propionate concentrations in ASD children compared with that in controls in the same fecal samples (25).…”
Section: Vol 77 2011 Lower Abundance Of a Muciniphila In Asd Childsupporting
confidence: 55%
“…The formaldehyde produced was measured colorimetrically with 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole as the chromogen. 23 Catalase activity was expressed as mg ⅐ nM Ϫ1 ⅐ min Ϫ1 protein.…”
Section: Measurement Of Malondialdehyde Superoxide Dismutase and Camentioning
confidence: 99%
“…One unit of SOD was defined as the amount of enzyme needed to exhibit 50% dismutation of the superoxide radicals. 23 SOD concentration was expressed as U/mg protein.…”
Section: Measurement Of Malondialdehyde Superoxide Dismutase and Camentioning
confidence: 99%
“…Reactive astrogliosisis is typically characterized by astrocyte proliferation and hypertrophy (MacFabe et al, 2008). Decreased or increased density of glial cells has been shown in many fundamental works on animal models that were aimed on research of irradiation consequences.…”
Section: Introductionmentioning
confidence: 99%